Development of a method for increasing the efficiency of processing different types of data in organizational and technical systems - Mahdi, Qasim Abbood; Shyshatskyi, Andrii; Voznytsia, Anastasiia; Plekhova, Ganna; Shostak, Serhii; Tulenko, Ihor; Semko, Ruslan; Zheliezniak, Denys; Momit, Alexander; Sova, Mykhailo (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the research is heterogeneous data circulating in organizational and technical systems. The subject of the research is the process of processing heterogeneous data. The problem addressed in the study is improving the responsiveness of heterogeneous data processing in organizational and technical systems while ensuring a specified level of reliability, regardless of the volume of data entering the system. The essence of the obtained results lies in the use of improved metaheuristic algorithms for processing heterogeneous data in combination with other approaches. The originality of the method lies in the use of additional improved procedures that allow for: – accounting for the degree of influence of destabilizing factors affecting the processing of heterogeneous data in an organizational and technical system, which makes it possible to consider the elements of the system that provide the highest reliability in heterogeneous data processing; – taking into account the initial speed of each agent in the swarm of the combined algorithm, which enables prioritization of the search in the corresponding search space (by elements and components of the organizational and technical system); – optimizing the topology of heterogeneous data processing circulating in the organizational and technical system; – considering the failed elements of the organizational and technical system that are unsuitable for heterogeneous data processing; – taking into account the influence of destabilizing factors both during the initial placement of the agents in the swarm of the combined algorithm and during the processing of heterogeneous data circulating in the organizational and technical system; – the ability to calculate the required number of computing resources that need to be engaged if the available computing resources are insufficient for performing calculations. An example of the application of the proposed method in processing heterogeneous data within an operational grouping of troops (forces) demonstrated an improvement in decision-making responsiveness by 13–15 % due to the use of additional procedures and ensuring a decision reliability level of 0.9